Kualifikasi Guru Qurâan Hadits di Madrasah - ., Srifariyati (Madaniyah, 2015)
Teacher is one of the factors determine the quality of education. The main task of the teacher is education and teaching in the school. One of the subjects of a clump of Islamic Education (PAI) is the Quran hadith. Al Quran and Hadith is a Muslim way of life, then learn the Quran Hadith is absolutely necessary, it is important for the teacher of al Quran hadith to have the qualifications or competence, so that learning aims can be achieved.Qualifications is special education to acquire a skill or expertise needed to achieve something, while teacher competency is the ability and authority of teachers in implementing his profession. Teachers al Quran hadith must have pedagogic competence, profesional competence, personality competence, and social competence, faithful, devoted, and good morals.Pedagogic competence is the ability to manage the learning. That includes in it is an understanding of the learners, the planning and implementation of learning, evaluation of learning outcomes, and the development of learners to actualize various potentials. Personal competencies or personality is the ability personality steady, stable, mature, wise, and authoritative, become role models for students, and noble. Profesional competence is the ability mastery learning materials widely and in-depth guides that enable learners to meet the standards of competence specified in the National Education Standards. Social competence is the ability of educators as part of the community to communicate and interact effectively with students, fellow teachers, staff, parents or guardians of students, and surrounding communities.Figure ideal teacher al Quran Hadits is the Prophet, because the Prophet is an example to his people, while the figure of the ideal teacher, because the Prophet develop material-spiritual aspect of man. Then, the teacher of al Quran hadith follows the pattern of prophetic education that reflects the values of a core of divinity with monotheism. Tauhidic education when implemented in daily life can not underestimate antropo-centric aspects, so that the dimensions of education includes the totality of theo-antropo-centric. Justification of aspects of divinity, or theo-centric earlier, taken from the source of revelation, while the conception of the faulty and humanity achieved through rational source. Briefly, a teacher al Quran hadith it can combine the material with the spiritual dimension, the physical with the spiritual, born with an inner, science with faith, and the mundane with the hereafter.